Model of religious conflict mechanism among Muslims in Malaysia - Ahmad Amri Zainal Adnan; Muhammad Hasbi Abdul Rahman (Penerbit Universiti Kebangsaan Malaysia, 2023)
This study was conducted to identify the critical factors that cause conflicts and division among the Muslim community in Malaysia. As the disputes among Muslims in Malaysia are acknowledged by religious scholars and national leaders to become more serious in recently, a formula for forming a more united and harmonious generation in diversity needs to be devised. Thus, the identification of the root cause of the problem and conflict mechanism can lead to religious harmony in society. This study tries to answer the question of why the phenomenon of religious conflict is formed in the Muslim community in Malaysia. This study uses a qualitative approach through a thematic analysis of transcripts from in-depth interviews. The study also conducts a systematic review of articles related to religious conflict from a social psychology perspective to support the argument. The result of the study is a model of the mechanism of religious conflict that uses a system model as the framework. Its impact on long-term national development is highly relevant as stated in Malaysia’s Vision for Shared Prosperity 2030.